Pengaruh Dana Perimbangan Terhadap Pertumbuhan Ekonomi dan Tingkat Kemiskinan di Provinsi Bali - Panji, I Putu Barat; Indrajaya, I Gusti Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 3, Maret 2016 (pp.316 - 384), 2016)
Economic growth and poverty reduction is an important indicator to see the successful development of a country. the success of development in the province of Bali's status as a tourist destination and has a fairly high income areas turned out to not be separated from the problem of poverty. This study aimed to analyze the influence of General Allocation Fund and the Special Allocation Fund for Poverty rate through Economic Growth Regency /City in Bali Province 2008-2013. The analysis technique used in this study is the technique of path analysis. The results showed the General Allocation Fund positive and significant impact on economic growth, but the Special Allocation Fund no significant effect on economic growth, the General Allocation Fund and the Special Allocation Fund had no significant effect on the level of poverty, but the economic growth a significant negative effect on the level of poverty, General Allocation Fund and the Special Allocation Fund indirect effect on the level of poverty through economic growth.
Keywords: General Allocation Fund; Special Allocation Fund; Economic Growth; Poverty Level